New exact solutions of the Dirac equation. IV; Soviet Physics Journal; Vol. 18, iss. 8 - Bagrov V. G.; Gitman D. M.; Meshkov A. G.; Simanchuk V. I.; Fedosov N. I.; Shapovalov A. V. Aleksandr Vasilyevich; Shapovalov V. N. (1975, 1975)
Title screen